WATER POWER GENERATOR FOR PUBLIC ROAD ILLUMINATION LIGHTS OF PADI VILLAGE MOJOKERTO - Akhmad solikin; Rohib Ilma Suktawan (Program Studi Teknik Elektro Universitas PGRI Adi Buana Surabaya, 2020)
Electricity problems in rural areas more and more electric power is needed. Until now, power plants that use water turbines are environmentally friendly electricity producers, so the potential for energy from the air needs to be utilized to address the demand for electricity. Therefore, the solution to this problem is to use the